1998
DOI: 10.1053/euhj.1998.1229
|View full text |Cite
|
Sign up to set email alerts
|

Intra-urban variations in incidence and mortality in myocardial infarction. A study from the myocardial infarction register in the city of Malmö, Sweden

Abstract: AimTo assess to what extent intra-urban variations and time trends of mortality in ischaemic heart disease are related to incidence of disease. Methods and ResultsIncidence and mortality data were retrieved from the myocardial infarction register in Malmö. Age-and sex-adjusted incidence varied between the 17 city areas from 469 to 681/10 5 (P=0·003), and mortality from 286 to 446/10 5 (P=0·017). Socio-demographic risk factors for ischaemic heart disease were more prevalent in high rate areas. About 70% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Vital status at the end of the follow-up was up dated on all individuals by data linkage with regional and national registers. 20 The completeness and validity of these registers have been documented in several other studies from the city. 20,31 Change of exposure is an inherent problem in long-term studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Vital status at the end of the follow-up was up dated on all individuals by data linkage with regional and national registers. 20 The completeness and validity of these registers have been documented in several other studies from the city. 20,31 Change of exposure is an inherent problem in long-term studies.…”
Section: Discussionmentioning
confidence: 89%
“…20 The completeness and validity of these registers have been documented in several other studies from the city. 20,31 Change of exposure is an inherent problem in long-term studies. Subjects who were diagnosed with hypertension, lipid disorders, diabetes mellitus or problematic drinking behaviour were referred for further evaluation and treatment, smokers were advised to quit, but received no further help to achieve that.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…3,33 In Malmö, the incidence of and mortality from MI have declined, 34 and 3-year survival after first MI has continuously improved. 6 Values are the age-adjusted annual incidence rates of first-ever stroke per 100 000 person-years (number of cases).…”
Section: Possible Explanation For Changing Trends In Stroke Incidencementioning
confidence: 99%
“…Previous studies from Malmö have shown that there are substantial differences in risk of CVD between residential areas with high and low proportion of immigrants (12)(13)(14)(15). The purpose of the present population-based study is to explore the relationship between country of birth and risk of HF hospitalizations after taking age, sex and socioeconomic indicators into account.…”
Section: Introductionmentioning
confidence: 99%